2022
DOI: 10.12688/gatesopenres.13361.2
|View full text |Cite
|
Sign up to set email alerts
|

Testing for sensory threshold in drinking water with added calcium: a first step towards developing a calcium fortified water

Abstract: Background: Food fortification is an effective strategy that has been recommended for improving population calcium inadequate intakes. Increasing calcium concentration of water has been proposed as a possible strategy to improve calcium intake. The objective of this study was to determine the sensory threshold of different calcium salts added to drinking water using survival analysis. Methods: We performed the triangle test methodology for samples of water with added calcium using three different calcium salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Also, supplementation may not be adequate for small children. 15,39 Adding calcium to water in combination with other strategies, such as food fortification, should be evaluated specifically for each population. 2,11,13 While planning an intervention to improve calcium intake in the population, vitamin D status should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, supplementation may not be adequate for small children. 15,39 Adding calcium to water in combination with other strategies, such as food fortification, should be evaluated specifically for each population. 2,11,13 While planning an intervention to improve calcium intake in the population, vitamin D status should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] A food fortification vehicle requires reaching the target population while ensuring that its promotion can be synergized with efforts to improve diet. 2,14,15 Water has the advantage of being universally consumed and promoting the consumption of water can be a part of public health strategies for healthier diets. 16,17 We have previously simulated the impact of different calcium concentrations of water using individual food intake data from six countries by assessing the gap between dietary calcium intake and recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a consumer panel of 54 individuals from Argentina, a recent acceptability study of three different calcium salts added to bottled water found that the sensory threshold for taste was 587 ± 131 mg/L of water for calcium gluconate, 676 ± 186 mg/L for calcium lactate, and 291 ± 73 mg/L for calcium chloride. 21 Assuming it can be made safe and accessible and that sensory acceptability findings from this small sample in Argentina would apply in other countries, drinking water could potentially be a good alternative vehicle to improve calcium in the diet. [24][25][26][27] This study, based on simulated diets using dietary data from the overall population, explored the potential of calcium-fortified wheat flour and water to complement the FBRs of local food sources of calcium in reaching the daily recommended Ca PRIs of four population groups (12-to 23-month-old and 4-to 6-year-old young children, adolescent girls, and NPNB women) across Bangladesh, Guatemala, and Uganda, where previous analysis showed that it was difficult or not possible to meet calcium intake targets using diets based on local foods alone.…”
Section: Introductionmentioning
confidence: 95%
“…Specific details on the mineral composition of location-specific drinking water are limited and usually missing in chemical composition tables, which creates challenges to assess the contribution of water on mineral intake. 20,21 Calcium levels in drinking water regulations are usually expressed in terms of a maximum level of water hardness. 22,23 Calcium bioavailability in water is high, similar to or higher than in dairy products.…”
Section: Introductionmentioning
confidence: 99%